An investigation into psychological factors that compel battered women to remain in abusive relationships in Vhembe District, Limpopo - Shivambu, Tivani Dainah (My University, 2015)
The study investigated the psychological factors that compel battered women to remain in abusive relationships. According to statistics in South Africa (SA) one in every five women is battered by her partner, and one in every four of all women in SA are assaulted by their partners weekly. The research approach was qualitative in nature. Sampling for the study was purposive and utilised eight participants who met the criteria for the investigation. The study was conducted at Tshilidzhini Hospital Trauma Centre and The Sibasa Victim Empowerment unit in Thohoyandou, Vhembe District in the Limpopo province. Data was gathered using a semi-structured questionnaire guide. Data was analysed, using Thematic Content Analysis (TCA), to gain an in-depth account of each participant’s experience of abuse. The results of the study indicate that cultural factors still play an important role in facilitating women abuse. The women in the study used religion, denial and avoidance, guilt and self-blame as coping mechanisms. Low self-esteem, depression, cognitive dissonance and relationship hope and commitment were identified as psychological factors compelling battered women to remain in abusive relationships. The study recommended that educational programmes and workshops on woman abuse be provided to empower women in rural areas.
Thesis (M.A. (Psychology)) -- University of Limpopo, 2015
Keywords: Battered women; Abusive relationships; Abused women -- South Africa -- Limpopo.; Women -- Abuse of -- South Africa -- Limpopo.; Family violence -- South Africa -- Limpopo.